The Relationship of Smoking Behavior to Bronchitis Incidence in Sawit Hulu Village, Sawit Seberang District in 2019 - Domaria; Firda Yanti; Neni Afnidar; Errick Azzuhri; Sarah Nabila Al Mufarid (Institute of Computer Science (IOCS), 2019)
Smoking is one habit that is difficult to break. Moreover, currently smoking has become a national problem, and even internationally. Smoking behavior seen from various points of view is very detrimental, both for oneself (active) and those around them (passive). The purpose of the study was to determine the relationship between smoking behavior and the incidence of bronchitis in Sawit Hulu Village, Sawit Seberang District in 2019 and to determine smoking behavior in Sawit Hulu Village, Sawit Seberang District, to determine the incidence of bronchitis in Sawit Hulu Village, Sawit Seberang District. To find out the relationship between smoking behavior and bronchitis incidence in Sawit Hulu Village, Sawit Seberang District in 2019.The results showed that from 38 respondents the majority of good behavior were 25 respondents (68.5%) and bad minority were 13 respondents (34.2%) and the majority of the incidence of Acute bronchitis were 24 respondents (63.2%) and chronic minority were 14. respondents (36.8%).